Analisis Asumsi-Asumsi pada Program Food Estate di Papua - Beltahmamero Simamora; Khairunnisah Lubis; Hadiyanti Arini (PERSPEKTIF, 2021)
The issue of the food crisis sticking out long before the Covid-19 pandemic occurred since 2008 and has become a hot topic discussed by regional and global institutions. The recommendation to maximize the private or corporate sector with the support of global scale financialization to move investment in the field of food production is one of the "goals" of the recommendation to create a large-scale food warehouse called a "food estate". This paper aims to analyze the assumptions of the Food Estate Program in Papua. Discussing the assumption that the assumptions of the offices tend to be late so that the importance level is low, there should be an effort to analyze it before there is a decision making, even if the MIFEE program from the central government. The assumption that the community feels disadvantaged by the existence of the MIFEE program, that the loss of forests due to deforestation and the loss of a foraging culture due to ethnocide has led to the disadvantaged community to give the MIFEE proposal a review. The presence of DPRD and NGOs is weak and only able to slow down the program, not until it is canceled. The government as the upper-right quadrant actor has clear strengths and important assumptions, because it is supported by economic and political plans and is oriented towards economic growth. The conclusion is that the assumption of the offices tends to be late even though the MIFEE program from the central government, the assumption of the people who feel disadvantaged by the existence of the MIFEE program, is that the presence of DPRD and NGOs is weak and it slows down the running of the program. The government as an actor in the right-hand quadrant has clear strengths and important assumptions.